Pemanfaatan Pendekatan Differentiated Instruction Dalam Meningkatkan Pemahaman Konsep Matematika Siswa Beragam Kemampuan di Sekolah Dasar - Ertanti, Devi Wahyu; Arifin, Slamet; Mardhatillah (IJPSE Indonesian Journal of Primary Science Education, 2024)
Differentiated instruction has emerged as a pivotal approach to addressing the diverse learning needs of elementary school students, particularly in enhancing mathematical concept comprehension. This study aims to investigate the impact of differentiated instruction on improving mathematical understanding among students with varying abilities in elementary schools. Utilizing a literature review method, this research synthesizes findings from peer-reviewed journals indexed in SINTA and Scopus over the past five years. The results reveal that differentiated teaching strategies, such as live worksheet-based e-LKPD, educational games like INDITGO-MATH, and learning stations, have significantly increased student comprehension by up to 32%. Furthermore, these strategies have been effective in boosting motivation and engagement, contributing to an inclusive and adaptive learning environment. Despite the evident benefits, challenges such as limited teacher training and preparation time persist (Pamungkas, 2024). To overcome these barriers, the integration of digital learning resources and intensive teacher training has proven to be a feasible solution. This study recommends that elementary schools implement differentiated instruction more widely, supported by adequate resources and continuous professional development. The findings underscore the importance of developing interactive learning materials that align with differentiated teaching to further optimize learning outcomes across varying student abilities.